REFLECTIVE MENTORING AND EFL STUDENT TEACHERS’ PROFESSIONAL IDENTITY: A FUNDS IDENTITY PERSPECTIVE - Nadhiratul Ulfa; Fauziah Fauziah; Zaiturrahmi Zaiturrahmi (ELITERATE : Journal of English Linguistics and Literature Studies, 2026)
This study highlights that although many studies have examined reflective mentoring in EFL teacher education, only a few studies have linked it with the Funds of Identity theory. This study aims to investigate the influence of reflective mentoring on the professional identity development of EFL student teachers. Using a qualitative case study design, this research involved eight EFL student teachers from the English Education Department at Jabal Ghafur University who were undergoing teaching practicums. Data were collected through reflective journals and semi-structured interviews, then analyzed using thematic analysis. Guided by the Funds of Identity framework, the findings indicate that reflective mentoring supports the development of self-awareness, self-confidence, pedagogical competence, and reflective thinking. The findings also showed that professional identity construction was influenced by several sources of identity, particularly social relationships with mentors and peers, past learning experiences, language-related experiences, personal values, and future aspirations. Among these sources of identity, social relationships emerged as the most dominant factor. This study implied that reflective mentoring can support the development of more reflective, confident, and competent EFL student teachers.